Routines as a Source of Change in Organizational Schemata: The Role of Trial-and-Error Learning - Rerup, Claus; Feldman, Martha S. (Academy of Management Journal, 2011)
Organizational routines are ubiquitous, yet their contribution to organizing has been underappreciated. Our longitudinal, inductive study traces the relationship between organizational routines and organizational schemata in a new research institution, Learning Lab Denmark. We show how trial-and-error learning can connect routines and schemata through a microfoundation of observable action. Our analysis (1) identifies two processes of trial-and-error learning and (2) strengthens theory about the coevolution of interpretive schemata and routines. By recognizing the complex relationship between routines and schemata and the role that trial-and-error learning processes play in this relationship, organizations can gain a previously overlooked tool for managing change.